A new species and a new record of Trischistoma Cobb, 1913 (Nematoda: Enoplida: Trischistomatidae) from Shanxi Province, China - Xu, Yu Mei; Zhao, Zeng Qi; Wang, Jian Ming (Zootaxa, 2015)
This paper describes a new species and gives a new record and a re-description of a known species of Trischistoma Cobb, 1913. Trischistoma taiguensis sp. nov. is characterized by having one pair of caudal setae on the tail; female body length of 562–699 µm, a = 35–42, b = 4.1–4.7, c = 11–14, c' = 3.9–4.6 and V = 79–82%. For the first time, Trischistoma pellucidum Cobb, 1913 is recorded from Shanxi Province, China. The phylogenetic relationships among species in the genus Trischistoma were analyzed using data from the SSU (small subunit) and D2/D3 expansion segments of the LSU (large subunit) rDNA sequences. These analyses confirmed that T. taiguensis sp. nov. and T. pellucidum differ from other known members of the genus for which sequences are available in GenBank.